Effect of Different Culture Conditions on Gene Expression Associated With Cyst Production in Populations of Artemia franciscana - Parraguez, Margarita (Frontiers in Genetics, 2022)
Artemia franciscana inhabits hypersaline environments in the Americas and has a well-adapted reproductive system that allows it to survive in these extreme conditions, represented by the production of diapause cysts (oviparous reproduction). This reproduction mode is controlled by numerous genes that are expressed in response to different environmental stressors, enabling this species to avoid population extinction. However, to date, the expression of these genes has not been sufficiently studied to clarify their levels in response to a combination of different environmental factors under controlled conditions. We analyzed the expression of eight genes related to oviparous reproduction (SGEG, Arp-CBP, artemin, BRCA1, p8, ArHsp21, ArHsp22, and p26) to determine their association with cyst production in two populations of A. franciscana with contrasting phenotypes, one with high (Barro Negro, BNE, Chile) and one with low (San Francisco Bay, SFB, United States) cyst production. Populations were cultured under controlled conditions of salinity (SAL, 35 and 75 ppt), photoperiod (PHO, 12L:12D and 24L:00D), iron concentration (IC, 0[Fe] and 5[Fe]), and microalgae diet (DIE; Dunaliella tertiolecta (DUN) and Tetraselmis suecica (TETRA)). Sixteen treatments were performed by combining the two conditions of each of the four factors. Data on nine reproductive parameters per female were recorded, including the percent of offspring encysted (%) (POE). The gene expression levels were analyzed by semiquantitative RT-PCR. The mean POE was significantly greater in BNE than in SFB (32.40 versus 12.74%, Mann–Whitney’s test, p < 0.05). Significantly upregulated expression of seven genes in BNE (more than twofold, p < 0.05) was observed in 38.28% of the treatments (e.g., DUN-75ppt-12L:12D-5[Fe] and TETRA-35ppt-12L:12D-5[Fe]). In SFB, seven genes showed significant differential expression, but most were downregulated in 29.69% of the treatments (e.g., DUN-75ppt-12L:12D-0[Fe] and DUN-75ppt-24L:00D-0[Fe]). Multiple regression analyses indicated that in BNE, five genes (SGEG, artemin, Arp-CBP, p8, and BRCA1) and three environmental factors (DIE, SAL, and IC) were important predictor variables for the POE response variable given that all of them were included in the highest-ranking models. In SFB, only two genes (ArHsp21 and artemin) and one environmental factor (SAL) were important explanatory variables in the highest-ranking models. It was concluded that the BNE population presented a characteristic gene expression pattern that differed from that of the SFB population. This pattern might be related to the marked oviparous reproduction of the BNE population. This gene expression pattern could be useful for monitoring the reproductive mode leading to diapause in Artemia and to assist with intensive cyst production in pond systems.